Confucianism and Firm Performance - Lisong Wang; Lisong Wang; Yongjie Zhang; LiNa Wang; Jingkai Fu (Frontiers in Physics, 2020)
This paper examines the impact of Confucianism on firm performance, taking Chinese listed companies from 2000 to 2018 as the research object. The results show that (1) Confucianism provides legitimacy for a company's profit-seeking behavior and therefore helps to improve firm performance; and (2) Confucianism can effectively improve the efficiency of supervision mechanisms but weaken the marginal contribution of incentive mechanisms to financial performance. This paper provides empirical evidence for the influence of Confucianism on firm performance, broadening the understanding of the role of informal institutions in company finance and enriching the theory of “culture and finance.”